Comparative life cycle assessment of glycerol valorization routes to 1,2- and 1,3-propanediol based on process modeling - Vanapalli, Kumar Raja; Nongdren, Lourembam; Maity, Sunil K.; Kumar, Vinod (American Chemical Society, 2024)
Crude glycerol, a high-volume byproduct of the biodiesel industry, has seen a significant surplus due to the industry’s rapid growth. It can be a promising feedstock for a range of high-value products via chemical and biochemical routes. This study thus elucidates the relative environmental performance of two prominent glycerol valorization technologies, i.e., catalytic hydrogenolysis to 1,2-propanediol and microbial fermentation (batch and fed-batch) to 1,3-propanediol, using a cradle-to-gate life cycle assessment (LCA). The LCA was performed using an experimental data-driven comprehensive process model to represent an industrial-scale biorefinery, handling 20 833 kg/h of glycerol. The LCA results identified cooling water (18-35.5%) and steam (15.2-33.7%) consumption in the distillation and glycerol sourcing (33.3-68.1%) as the critical environmental hotspots, which should be focused on while designing the process. The fed-batch fermentation process was environmentally more benign, with significantly lower environmental impacts than hydrogenolysis (by 35.2%) and batch fermentation (by 48.2%). Integrating effective process heat recovery using pinch technology reduced the overall environmental impacts by 4.9-11.2%. The environmental performance of the overall processes varied substantially (2.4-62.1%) with changes in glycerol sourcing and production methods. Therefore, energy and material recycling with sustainable water and glycerol sourcing can improve the sustainability of the overall process.
Keywords: Biorefinery; Glycerol; Life Cycle Assessment; Propanediols; Sensitivity; 4004 Chemical Engineering; 3401 Analytical Chemistry; 40 Engineering; 34 Chemical Sciences; 12 Responsible Consumption and Production